Forensic Identification of Blood Types in Pear (Pyrus bretschneideri) Fruit Bitemark - Aliviameita, Andika; MAR, Mieke Sylvia; Yudianto, Ahmad (Folia Medica Indonesiana, 2018)
Blood type in saliva can be examined through bitemarks on an object left at the crime scene in a crime case as a screening test of suspected perpetrators. Saliva deposited at the bite contains glycoproteins which can carry blood type ABH antigens expressed in the salivary glands and excreted in saliva. Salivary examination is influenced by various external factors that damage saliva, one of which is the duration of exposure to room temperature in a certain period of time. This study aimed to determine differences in protein levels and blood group agglutination titers in (Pyrus bretschneideri) pear bitemark saliva during room temperature exposure within 30, 60 and 90 minutes. This type of study was experimental laboratories with time series design. The samples used were 18 pear bitemarks from 6 individuals who had blood groups A, B and AB then incubated for 30, 60 and 90 minutes. Analysis of protein content using trizol reagent was determined spectrophotometrically, while blood group examination used inhibition absorption method. Anova test showed significant difference between groups of 30 minutes exposure duration with 60 minutes and 90 minutes exposure group (P<0.05; 95% confidence interval). The Pearson correlation obtained the results of -0.739, indicating correlation that the longer exposure to room temperature, the lower the protein content. The results showed that there was a decrease in salivary protein levels and blood group agglutination titers. Salivary protein levels were still detected in the time range of 30, 60 and 90 minutes, so that blood type can still be examined from saliva in bitemarks on pear fruit.